2013
DOI: 10.1111/jns5.12008
|View full text |Cite
|
Sign up to set email alerts
|

Corneal confocal microscopy is efficient, well‐tolerated, and reproducible

Abstract: In order to develop an efficient, reproducible, and well-tolerated protocol for assessing corneal innervation, 11 normal subjects underwent corneal confocal microscopy (CCM) using a Heidelberg Retinal Tomography III microscope. Five standardized locations were sampled in the left eye and one centrally in the right. The protocol was repeated 1-4 weeks later. A blinded technician measured nerve fiber length (NFL) and tortuosity coefficient (TC). The relationship between image location and NFL and TC was assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 11 publications
0
27
0
1
Order By: Relevance
“…Images that included components of both the nerve fiber layer and epithelium or endothelium were not used for analysis. Images with artifacts derived from compression of the eye by the microscope were also excluded from this analysis 16. A fully automated image analysis algorithm was used to quantify corneal nerve fiber density (CNFD), corneal nerve branch density (CNBD), and corneal nerve fiber length (CNFL) using purpose‐written, proprietary software (ACCMetrics; M.A.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Images that included components of both the nerve fiber layer and epithelium or endothelium were not used for analysis. Images with artifacts derived from compression of the eye by the microscope were also excluded from this analysis 16. A fully automated image analysis algorithm was used to quantify corneal nerve fiber density (CNFD), corneal nerve branch density (CNBD), and corneal nerve fiber length (CNFL) using purpose‐written, proprietary software (ACCMetrics; M.A.…”
Section: Methodsmentioning
confidence: 99%
“…It has also been widely used to evaluate diabetic neuropathy in multiple studies10 demonstrating that this technique is a viable surrogate endpoint for early diagnosis,11 stratification of neuropathy severity,12 and assessing the response to treatment 13. This technique is highly reproducible14, 15 and well‐tolerated 16. An automated and standardized image analysis method for quantification of corneal nerve morphology has also been developed 17, 18…”
Section: Introductionmentioning
confidence: 99%
“…However, since then, a burgeoning literature shows that IVCCM can quantify DN ( Table 2). [39][40][41][42]44,56,57 We have demonstrated that IVCCM quantifies early small nerve fiber damage 39,42,65 with good sensitivity and specificity 39 (Figure 2). Others have confirmed that IVCCM detects mild neuropathy, 38 and corneal nerve fiber length in particular has a high sensitivity (91%) and specificity (93%) for identifying diabetic sensorimotor polyneuropathy.…”
Section: Corneal Nerve Changes In Diabetic Neuropathymentioning
confidence: 94%
“…CIPN [3] may reveal corresponding ocular changes in the corneal [340,341] and nerve layers of the retina [342] similar to the nerve damage seen in diabetes. Conducing CCM and OCT assessments may allow researchers to investigate the relationship between the nerves of the eye and the peripheral nerves of the body in patients who undergo chemotherapy with neurotoxic agents.…”
Section: Rationalementioning
confidence: 99%
“…Basically the CCM is a high magnification microscope that can be used to look at the nerves in the front of the eye. This technique has been validated as a neuropathic diagnostic tool particularly for diabetic patients [340] and has been selected to trial for CIPN assessment.…”
Section: Corneal Confocal Microscopymentioning
confidence: 99%